Site and incidence of birth canal lacerations from instrumental delivery with mediolateral episiotomy - Kenro Chikazawa; Junko Ushijima; Kenjiro Takagi; Eishin Nakamura; Koki Samejima; Kanako Kadowaki; Isao Horiuchi (Elsevier, 2016)
Objective: Instrument-assisted vaginal delivery is a significant risk factor for birth canal lacerations. Although many obstetricians recently are recommending restrictive rather than a routine episiotomy, reports have shown restrictive episiotomy to be associated with more extensive anterior birth canal trauma compared with routine episiotomy. Materials and Methods: We retrospectively reviewed 110 cases of forceps and vacuum deliveries and investigated the site of birth canal lacerations. Birth canal lacerations were divided into four sites according to direction-anterior, ipsilateral, contralateral, and posterior. Results: The frequency of lacerations were, from most to least, posterior (34%), lateral (21.7%), and anterior (1.9%). Moreover, among the lateral lacerations, they were more frequent in the contralateral side of episiotomy than the ipsilateral side (18.9% vs. 4.7%, p < 0.01). Conclusion: Our results indicate that caution is also needed concerning not only the anterior site, but also the contralateral site of an episiotomy to prevent laceration in an instrument-assisted vaginal delivery.